Beyond the syndemic: condom negotiation and use among women experiencing partner violence. Issue 4 (3rd April 2017) - Peasant, Courtney; Sullivan, Tami P.; Weiss, Nicole H.; Martinez, Isabel; Meyer, Jaimie P.
ABSTRACT: Background: HIV and sexually transmitted infections (STIs) disproportionately affect women who experience intimate partner violence (IPV). Objective: The current study (1) applied a syndemic framework to study the collective effects of problematic drug use, hazardous drinking, depression, and posttraumatic stress disorder (PTSD) on fear of condom negotiation, condom negotiation, and condom use and (2) evaluated condom negotiation (controlling for fear of condom negotiation) as a mediator of the association between syndemic severity and condom use among low-income IPV-exposed women. Methods: Participants were 158 women living in the community and experiencing ongoing IPV who completed face-to-face, computer-assisted interviews. Results: Almost three-fourths of the participants reported problematic drug use, hazardous drinking, depression, and/or PTSD; many of these factors were correlated, indicating a syndemic. Multivariate logistic and linear regression analyses revealed associations between syndemic severity and fear of condom negotiation (OR = 1.57, p = .02), condom negotiation ( β = −8.51, p = .001), and condom use ( β = −8.26, p = .01). Meditation analyses identified condom negotiation as a mediator of the association between syndemic severity and condom use (effect = −6.57, SE = 2.01, [95% CI: −10.66, −2.77]). Conclusions: Results fill a critical gap in previous research by identifying condom negotiation as a mechanism through which this syndemic affects condom use. Prevention and intervention programs should consider addressing condom negotiation to reduce sexual risk among this high-risk population. Further, because IPV-exposed women may experience fear related to condom negotiation, it is critical that prevention and intervention efforts for this population offer skills to safely negotiate condom use, increase condom use, and reduce STI and HIV risk.